1963
DOI: 10.1126/science.140.3564.312
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Enhancement by Protein Films

Abstract: Evaporation of water takes place more rapidly from buffered solutions of ovalbumin or hemoglobin than from solutions of certain surface-active agents or from buffer alone. The effect appears to be connected with adsorption of protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
1986
1986

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…7, July 1964 sorption (513) and a comparative study of liquid and vapor permeation through various polymer films (514) have been reported. James, et al, commented on the enhancement of evaporation by protein films as compared with solutions of certain surfactants (515). A new interface balance for studying films at the oil-water interface was described (516).…”
Section: A Definite Interaction Hasmentioning
confidence: 99%
“…7, July 1964 sorption (513) and a comparative study of liquid and vapor permeation through various polymer films (514) have been reported. James, et al, commented on the enhancement of evaporation by protein films as compared with solutions of certain surfactants (515). A new interface balance for studying films at the oil-water interface was described (516).…”
Section: A Definite Interaction Hasmentioning
confidence: 99%